Electrical properties of 6.3 nm RF oxygen plasma oxide grown near room temperature with in situ dry cleaning of Si surface - Chanana R.K.; Upadhyay H.N.; Dwivedi R.; Srivastava S.K. (My University, 2025)
6.3 nm RF oxygen plasma oxide is grown near room temperature in a barrel reactor at 1.0 torr dynamic pressure and 70 W RF power with an in situ effective dry cleaning process preceding the oxide growth step. The as-grown oxide is very uniform and reproducible in thickness (6.3±0.3 nm). The as-grown oxide after post-oxidation anneal in 6% O2N2 ambient at 600°C for 30 min has 10 times more static sheet resistance just before the onset of FN emission (5 MV/cm) and has more dynamic sheet resistance at FN voltages than the RTO and furnace oxide. It shows a low leakage current density of 1 × 10-8 A/cm2 at FN onset field of 5 MV/cm, but exhibits low Eb in the 6-7 MV/cm range. It also shows high Nf of 1.5-3.0 × 1011 cm-2 and midgap Nit of 5-7 × 1011 cm-2 eV-1. © 1995.